Proceedings of the 2022 Annual ACM-SIAM Symposium on Discrete Algorithms (SODA) 2022
DOI: 10.1137/1.9781611977073.42
|View full text |Cite
|
Sign up to set email alerts
|

A Sublinear Bound on the Page Number of Upward Planar Graphs

Abstract: The page number of a directed acyclic graph G is the minimum k for which there is a topological ordering of G and a k-coloring of the edges such that no two edges of the same color cross, i.e., have alternating endpoints along the topological ordering. We address the long-standing open problem asking for the largest page number among all upward planar graphs. We improve the best known lower bound to 5 and present the first asymptotic improvement over the trivial O(n) upper bound, where n denotes the number of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…(E.g., Figure 2 depicts such an example.) Superseding previous results [21], Jungeblut, Merker and Ueckerdt [34] recently gave the first sublinear upper bound for all upward planar graphs by showing that every n-vertex upward planar graph G has stack number sn(G)…”
Section: Related Workmentioning
confidence: 68%
See 2 more Smart Citations
“…(E.g., Figure 2 depicts such an example.) Superseding previous results [21], Jungeblut, Merker and Ueckerdt [34] recently gave the first sublinear upper bound for all upward planar graphs by showing that every n-vertex upward planar graph G has stack number sn(G)…”
Section: Related Workmentioning
confidence: 68%
“…A slight generalization, namely whether all upward planar graphs have bounded stack number, is considered to be one of the most important open questions in the field of linear layouts [21,41,34]. It is known to hold for upward planar 3-trees [21,41].…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Heath and Pemmaraju [16] showed that there exist planar DAGs whose pagenumber is linear in the input size. Certain subfamilies of planar DAGs, however, have bounded page-number [1,6,10,18], while recently it was shown that upward planar graphs have sublinear page-number [20], improving previous bounds [12]. From an algorithmic point of view, testing whether a DAG has page-number k is NP-complete for every fixed value of k ≥ 3 [7], linear-time solvable for k = 1 [16], and fixed-parameter tractable with respect to the vertex cover number for every k [6] and with respect to the treewidth for st-graphs when k = 2 [7].…”
Section: Introductionmentioning
confidence: 99%
“…There are no existing worst-case results for dynamic upward embeddings and no results for dynamic upward embeddings subject to flips in the embedding. The study of upward planar graphs continues to be a prolific area of research, including recent developments in parameterized algorithms for upward planarity [10], bounds on the page number [23], morphing [26], and extension questions [8,25]. In particular, it can be tested in O(n 2 ) time whether a given drawing can be extended to an upward planar drawing of an n-vertex single-source directed graph G [8].…”
Section: Introductionmentioning
confidence: 99%